World Water Day 2024: Invest in women for peace and water security - Ringler, Claudia (International Food Policy Research Institute, 2024)
The theme of this year’s World Water Day (March 22), “Water for Peace,” could not come at a more opportune time. Global water, food, and humanitarian crises have reached near-unprecedented levels: As a 2023 conference of the Pontifical Academy of Sciences concluded, “The world is facing the highest number of violent conflicts since the Second World War. These conflicts are major triggers of humanitarian and food crises, reducing access to production factors, social safety nets and trade, and causing forced displacement.” More on World Water Day 2024 from IFPRI’s Claudia Ringler.